(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Fibrillation of amyloid Aβ (1-42) and Aβ (1-40) peptides (Aβs) is considered as one of causes of Alzheimer’s disease. In the present work we studied the influence of some plant preparations on the aggregation state of these peptides, evaluated by fluorescence of thioflavin T-containing samples. The abilities of some preparations to inhibit the self-aggregation of Aβs and to disaggregate their preformed aggregates were demonstrated. For somecases, IC50 values in these processes were evaluated. Based on the obtained data we recommend: a) frequent use of these plants by persons at risk group; b) clinical evaluating their extracts as sources of neurodegeneration preventing agents.